DFT-NEGF Simulation Study of Co2FeAl-MgO-Co2FeAl Magnetic Tunnel Junctions Under Biaxial Strain - Noh, Seongcheol; Sanvito, Stefano; Shin, Mincheol (IEEE transactions on magnetics, 2022)
Conventional spin-transfer torque-based magnetoresistive random access memory (STT-MRAM) with CoFeB electrodes has great potential as universal memory. However, state-of-the-art STT-MRAM technology has encountered the issues such as high writing current density and low thermal stability for scaling down to 1× nm. Heusler alloy has been suggested as an alternative to resolve these problems by significantly reducing the Gilbert damping constant while preserving approximately 100% spin polarization. In particular, L2_{1} -ordered Co 2 FeAl (CFA)-based magnetic tunnel junction (MTJ) exhibits outstanding half-metallicity and perpendicular magnetorcystalline anisotropy characteristics arising from Co(Fe)-O orbital hybridization at the interface. In this work, we investigate the biaxial strain effects of CFA-based MTJ by adjusting in-plane lattice constants from −4% to +4%. Our density functional theory - nonequilibrium Green's function (DFT-NEGF) calculations present that FeAl-O interfaced MTJ shows a converged tunneling magnetoresistance (TMR) ratio under compressive strain while Co 2 -O interfaced MTJ shows strain-sensitive TMR ratio under both compressive and tensile strain. The difference in the current-density trends for the two types of MTJs is mainly attributed to the additional state arising from Fe-O bonding. Our results emphasize the careful control of straintronic techniques on CFA-MTJs.